European Music Archaeology Project (EMAP): Ein internationales Kooperationsprojekt, gefördert durch die EACEA - Both, Adje (e-Forschungsberichte des DAI, 2023)
The European Music Archaeology Project (EMAP) is an international cooperation project funded by the Education, Audiovisual and Culture Executive Agency of the European Union for the period of five years (summer 2013 to summer 2018), and to which the Orient Department of the German Archaeological Institute is one of ten cooperation partners. The goal of the project is to combine research on the musical instruments of the archaeological cultures of the European continent, with special reference to the possible exchange of musical knowledge between individual cultures and through the times, and to present the results in a travelling multimedia exhibition. The study of manufacturing techniques and possible playing techniques in the course of the project results in playable replicas for the exhibition and concerts.